The Relationship between Teacher Learning Methods in Teaching and Student Learning Motivation with Learning Outcomes in PAI Subjects at SDN Bugel 01 Polokarto - Ria Putranti Arwitaningsih; Retno Wahyuningsih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
One important part of the learning process is the teacher's role in choosing learning methods and increasing students' motivation to learn. In addition to providing and sharing knowledge, teachers are also responsible for increasing students' motivation to learn: It is undeniable that students learn very differently and have their own learning styles. Therefore, it is important for teachers to always provide appropriate learning methods and motivation to their students so that they are always eager to learn and are able to become students who excel and develop themselves optimally. The learning process will be successful if students have the desire to learn. Teachers must foster students' best desire to learn. Teachers must be creative to encourage students to learn. Learning motivation is the reason why learning activities are interesting for students.